The wife : a novel - Wolitzer, Meg (New York : Scribner, 2004)
On the eve of her husband's receipt of a prestigious literary award, Joan Castleman, who has put her own writing ambitions on hold to support her husband, evaluates her choices and decides to end the marriage.
Reprint. Originally published: 2003.